The determinants of the usage of accounting information systems toward operational efficiency in industrial revolution 4.0: Evidence from an emerging economy - Pham Quoc Thuan; Nguyen Vinh Khuong; Nguyen Duong Cam Anh; Nguyen Thi Xuan Hanh; Vo Huynh Anh Thi; Tieu Ngoc Bao Tram; Chu Gia Han (Economies, 2022)
The purpose of this study is to determine the factors affecting the application of accounting information systems (AIS) in small and medium enterprises (SMEs) in Vietnam. Drawing upon the Technology-Organization-Environment (TOE) theoretical framework, Diffusion of Innovations theory (DOI), and Resource-based theory (RBV), we proposed a research model to investigate the antecedents and influence of AIS usage in Vietnamese SMEs. This study used an online survey of individuals who work in Vietnamese SMEs for data collection. The result was assembled by applying the PLS-SEM model to test the proposed hypotheses based on 132 valid responses. First, the factors that have a significant impact on AIS usage are as follows: relative advantage; owner/manager commitment; and impact of COVID-19. Second, the research results also confirm that there is a positive relationship between AIS usage and AIS effectiveness; AIS performance has a positive impact on business performance. Research implications are to help business owners and leaders decide whether to use AIS to strengthen the company's position and reduce the burden on departments, particularly the accounting department.
Keywords: 330; accounting information systems (AIS); AIS effectiveness; AIS usage; COVID-19